SYSTEM DESIGN BUREAU OF SUPPLIES OF GOODS IN GENERAL SECRETARIAT GENERAL OF THE MINISTRY OF PUBLIC WORK - Muhammad Auliya; Irwan Bastian, SKom, MM (Jurnal Sistem Informasi, 2000)
Inventory System at the Secretariat General of General Bureau of the Public Works Department aims to replace the data report form which is still ineffective manual data report form with computers. Computerized systems will be used as new input for the agencies concerned so that the making of the report data is done efficiently, quickly and precisely and can help reduce errors from routine work, can also easily provide the necessary information on matters relating to the Supply of Goods .